48. PoTS: Long term follow-up of an Italian cohort. Issue 4 (April 2016) - Barbieri, F.; Bongiovanni, L.G.; Fondrieschi, L.; Monaco, S.
Abstract : Postural Tachycardia Syndrome (PoTS) is an intermittent autonomic dysfunction characterized by orthostatic intolerance and a heart rate (HR) increase of at least 30 bpm, or a HR  ⩾ 120 bpm during standing. We reviewed clinical and neurophysiological characteristics and outcome after a long term follow-up of our cohort. Patients underwent clinical assessment, standardized autonomic testing and validated questionnaires to determine the severity of autonomic symptoms. The majority of our patients are young female, without either neuropathic features or a hyperadrenergic subtype. We found normal responses to Ewing tests and an increase of LF in the power spectrum of R–R interval and diastolic BP, during head–up tilt. In the same way total peripheral resistances (TPR) were maintained, even with differences among subjects. This indicates intact, although enhanced, baroreflex function. A coexisting tendency to autonomic mediated syncope was found in some patients. Orthostatic symptoms improved in most patients and half of them are now free of therapy and asymptomatic. The treatment consisted in different combinations of beta-blockers, exercise training and increased water intake. Our data agrees with a generally favorable prognosis in patients with POTS, if correctly diagnosed and treated, supported by the absence of structural damage of ANS.